1984
DOI: 10.1007/bf02540814
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and processing of cottonseed oil obtained by extraction with supercritical carbon dioxide

Abstract: Extraction of flaked cottonseed with supercritical carbon dioxide at temperatures of 50-80 C and pressures of 8,000-15,000 psi yields an improved crude cottonseed oil compared to those obtained by conventional solvent or expeller processes. Improvements include lighter initial color, less refining loss and lighter refined bleached colors. Crude cottonseed oils obtained by supercritical fluid extraction require less refining lye and show less tendency to undergo color fixation while in storage. ABSTRACTCrude oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 6 publications
1
22
0
2
Order By: Relevance
“…Therefore, the incomplete SCCO 2 extraction, as occurred in this study, can result in an oil low in polar components such as the pigments. Consistent with this study, the studies of Friedrich et al [7] and List et al [18] and cottonseed oils, respectively, showed that oils extracted with SCCO 2 were lower in pigments than oils extracted by organic solvents. As observed in this study, Friedrich and Pryde [8] also indicated that cottonseed, wheat germ and bran oils extracted by SCCO 2 were lighter in color, which was due to the lower concentration of pigments in such extracts.…”
Section: Chemical Characterization Of Extracted Oilssupporting
confidence: 88%
“…Therefore, the incomplete SCCO 2 extraction, as occurred in this study, can result in an oil low in polar components such as the pigments. Consistent with this study, the studies of Friedrich et al [7] and List et al [18] and cottonseed oils, respectively, showed that oils extracted with SCCO 2 were lower in pigments than oils extracted by organic solvents. As observed in this study, Friedrich and Pryde [8] also indicated that cottonseed, wheat germ and bran oils extracted by SCCO 2 were lighter in color, which was due to the lower concentration of pigments in such extracts.…”
Section: Chemical Characterization Of Extracted Oilssupporting
confidence: 88%
“…But all commercially extracted crude cottonseed oils are extremely dark due to co-extraction of an appreciable amount of gossypol and other pigments along with the oil. Crude cottonseed oil contains around 0.21% gossypol depending on the extent of heat treatment of the seed prior to extracting and expelling (List, Friedrich, & Pominski, 1984). Besides imparting colour to the oil, these pigments are toxic, which makes it necessary to impart intensive refining, clarification, rerefining, strong bleaching or a combination of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work published on SFE in the food processing industry has dealt with extraction of vegetable oils (Bulley, Fattori, Meisen, & Moyls, 1984;Christianson et al, 1984;Dakovic, Turkulov, & Dimic, 1989;Hierro & Santa-Maria, 1992;Lee, Bulley, Fattori, & Meisen, 1986;List, Friedrich, & Pominski, 1984;Stahl, Schü ltz, & Mangold, 1980;Taniguchi, Tsuji, Shibata, & Kobayashi, 1985). Supercritical carbon dioxide (SC-CO 2 ) has been established as a good alternative solvent for several lipid processing operations such as separation of FFA from vegetable oils, separation of polyunsaturated fatty acids (PUFA) from animal lipids, refining and deodorization of vegetable oil, fractionation of glycerides, recovery of oil from oil bearing materials, deoiling of lecithin and decholesterolization and delipidation of food products (Mukhopadhyay, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The oil can be obtained from cottonseeds by mechanical pressing, solvent extraction, and supercritical fluid extraction (Liauw et al, 2008;Bhattacharjee et al, 2007;List et al, 1984). The quality of oil extracted by mechanical pressing or squeezing in an expeller press is inferior and has a limited recovery of only 94-95%.…”
Section: Introductionmentioning
confidence: 99%